Dominio de la gestión de proyectos de TI - Salazar Villafuerte, Noemi Yolanda (2022)
The current job has as objective highlight the main achievements gotten through of my professional career line in the field of the System Engineering particularly in the direction of technological projects developed under the traditional approach as well as projects oriented to the agile framework. First, it is important to mention that all technological change will generate controversies, discussions and uncertainty, due to the afraid about what could happen when these changes would be implemented, expressing resistance to them. Based on that, the role that we play is crucial because will be the best allied with the high executive level reenforcing to the rest of the areas of the company the main benefits that will generate in each collaborator, bringing an accurate support to the managers during the development of this digital transformation process. Indeed, the support of a system engineer will generate value to the business because of the implementation of innovative, solid and confidence systems in a market which is each time more exigent and competitive, also defining our processes, tools, and methodologies that we will allow us to achieve a better management and coordination between the members of the project team, so they can have the same visibility of the objectives and goals that require to be committed. Definitely all that was mentioned above is not an easy task, because they are not only implied the knowledge field, but also the development of soft and hard skills learned throughout our career, so they can be complemented with each knowledge acquired as the project management, analysis and information security, service agreement level (SLA), technological tools domain, together with a leadership style and the development of effective communication to resolve conflicts, our professional ethic and all that allow us to improve our teamwork and the performance of each collaborator towards the accomplishment of the goals of the organization.